Susceptibility of three indigenous Indonesian fish species: mahseer (Tor soro), snakehead (Channa striata), and bagrid catfish (Hemibagrus nemurus) against parasites infection - Sumiati, Tuti; Taukhid, Taukhid; Andriyanto, Septiyan; Wadjdy, Edy Farid (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
AbstractÂ Mahseer